PENCITRAAN PEREMPUAN DALAM TEKS DRAMA SYAHRAZĀD KARYA TAUFῙQ AL-CHAKῙM (KAJIAN FEMINISME) - Eva Farhah, Ervina Pradestya Indriyani (Arabic Literature Department, 2018)
Woman’s images are images, dreams, or thoughts about women. The image or image of woman also varies in character. Indirecly, the character of the female figure will give an image, a shadow about the woman’s personality. The orientation of the talk about the image of women rests on the issue of the world view, the attitudes and the behavior of the woman. In this article, the images of woman contained in the Syahrazād, work of Taufīq Al-Chakīm are analyzed. The study of feminism and qualitative methode was used. The results of the study suggest that the images of woman contained in the drama text are, first; the image of women in their relationship with God, second; the image of women in relation to themselves, and the third; the image of women in relation to other humans.